CONTEMPORARY INTERPRETATION OF RELIGIOUS MODERATION IN THE QUR'AN: THOUGHT ANALYSIS QURAISH SHIHAB AND ITS RELEVANCE IN THE INDONESIAN CONTEXT - Munandar, Siswoyo Aris; Amin, Saifuddin (Universitas Muhammadiyah Surakarta, 2023)
Tafsir al-Misbah succeeded in combining the presentation of the surahs of the Koran with the al-adabi al-ijtima'i style with the correlative tahlili method. That is, Tafsir al-Misbah, even though it has an adabi al-ijtima'i pattern (a socio-community cultural style), does not leave a unified message in every surah of the Qur'an. The Quraish Shihab style of thought and its distinctive tendencies have sufficiently colored the discourse on al-Qur'an studies in Indonesia. This study attempts to describe the concept of wasathiyah Quraish Shihab from his works. This study uses a qualitative approach to the type of library research. The primary data is Quraish Shihab's book on Moderate Islam. In the thought of religious moderation, Quraish Shihab, namely the middle position makes humans not take sides to the left and to the right. Second, the understanding of ummatan wasathon in the concept of wasathiyyah with a middle meaning in the view of God and the world. Wasathiyah also contains the main principles of fairness, balance and tolerance. Islam as a religion with the highest number of adherents requires its adherents to have tolerance in society, protect minorities, and give freedom to the majority to worship as they believe. The Qur'an has explained the need to have a tolerant attitude in several of its verses, which later these verses were understood in various ways by mufassir, one of whom was Quraish Shihab.